2018
DOI: 10.1007/s10846-017-0750-z
|View full text |Cite
|
Sign up to set email alerts
|

Development of a New Hydraulic Ankle for HYDROïD Humanoid Robot

Abstract: For humanoid robots, design of the ankle mechanism is still open research problem since high torque is required while compact structures have to be maintained. This paper investigates an enhanced design of 3 degree-of-freedom hydraulic hybrid ankle mechanism. The design is based on (US9327785) [1]. Using a hybrid kinematic structure with hydraulic actuation, allows us to reach a slender humanoid ankle shape while enabling the high torque performances required for stable walking. Performances analysis of the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…[5] Hydoïd [6] is a real-life humanoid robot whose purpose is to contribute to improving the understanding of locomotion, the phenomenon of human motion. Humanoids on a Hydraulic Drive [7] can accomplish full spectrum of heavy and useful tasks, replacing people in environments that require them. HOPALALA is an open platform humanoid robot that users can adapt to their own needs.…”
Section: Humanistic Approach Of Biomimetic Roboticsmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] Hydoïd [6] is a real-life humanoid robot whose purpose is to contribute to improving the understanding of locomotion, the phenomenon of human motion. Humanoids on a Hydraulic Drive [7] can accomplish full spectrum of heavy and useful tasks, replacing people in environments that require them. HOPALALA is an open platform humanoid robot that users can adapt to their own needs.…”
Section: Humanistic Approach Of Biomimetic Roboticsmentioning
confidence: 99%
“…[5] is a real-life humanoid robot whose purpose is to contribute to understanding of locomotion, the phenomenon of human motion. a Hydraulic Drive [7] can accomplish full spectrum of heavy and eplacing people in environments that require them. The Virtual Armchair Project (FUI Ile de France with EDF and CEREMH, 2014/2018) was developed as a result of the FUI AccesSim project focused on assessing the virtual reality of urban accessibility.…”
Section: Humanistic Approach Of Biomimetic Roboticsmentioning
confidence: 99%
“…They showed that moving in the different directions was possible but displacement on complex environment requires another approach in this regard. Also, hydraulic and pneumatic methods require at least a powerful and high weight pump or compressor which they will clearly make the noise pollution 14 – 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Research has been ongoing on developing an integrated electrohydraulic actuator for robotic applications. The first prototype was presented in Alfayad et al 35,41 further research concerning the mathematical modeling and system identification was done in Abdellatif et al 42 The first IEHA actuator needed an actual pressure of 25 bar to produce a flow rate of 0.024 l/min against an expected theoretical flow of 0.13 l/min at the same pressure. A motor speed of 3000 rpm is used for both cases.…”
Section: Introductionmentioning
confidence: 99%